Effects of Xinjiang wild cherry plum (Prunus divaricata Ledeb) anthocyanin-rich extract on the plasma metabolome of atherosclerotic apoE-deficient mice fed a high-fat diet - Shen, Jing; Li, Xing; Zhang, Xin; Li, Zhen; Abulaiti, Gulisitan; Liu, Yang; Yao, Jun; Zhang, Pei (Frontiers in Nutrition, 2022)
It is well known that many vegetables and fruits have abundant polyphenols, such as anthocyanins, which benefit many cardiovascular diseases due to their anti-oxidative and anti-inflammatory effects. To explore the protective effect of anthocyanin on atherosclerosis from a metabolic perspective, alterations in plasma metabolic profiling of apoE-deficient (apoE-/-) mice in response to treatment with anthocyanin extracts derived from Xinjiang wild cherry plum (Prunus divaricata Ledeb) peel was investigated through UHPLC-Q-TOF/MS. The mice were fed with normal diet or high-fat diet supplementation with or without anthocyanin extracts (ACNE, 75, 150, 250 mg/kg body weight) for 18 weeks, corresponding to control (Con), model (Mod), treatment group (low dose: LD, medium dose: MD, high dose: HD), respectively, along with a positive control group (posCon, treatment with Atorvastatin, 0.003 mg/kg body weight). The results showed that ACNE could significantly enhance the antioxidant capacity and lower the plasma lipid, but have no evident influence on body weight of apoE-/- mice. A series of differential metabolites, predominantly related to lipid metabolism, were identified, including docosahexaenoic acid, palmitoyl ethanolamide, stearoylcarnitine, L-palmitoylcarnitine, indoxyl sulfate (IS), 1-palmitoyl-lysophosphatidylcholine, phenylacetylglycine (PAGly), and so on. Among these, both IS and PAGly were host-microbial metabolites. These differential metabolites were mainly enriched in the pathway of glycerophospholipid metabolism and linoleic acid metabolism. Several important enzymes related to glycerophospholipid metabolism such as LCAT, LPCAT, GPCPD1, PLA2G1B, PPARG, LIPE, PNPLA2, AGPAT1, ENPP2 were recognized as underlying targets for anti-atherogenic effects of ACNE. These findings suggest that ACNE derived from Xinjiang wild cherry plum exhibits protective effects against atherosclerosis via modulating glycerophospholipid metabolism.